How institutions matter for international business: Institutional distance effects vs institutional profile effects - van Hoorn, André; Maseland, Robbert (Journal of International Business Studies, 2016)
Extant institutional research has failed to make a distinction between the effects of institutional profile and institutional distance on MNEs. The problem stems from the fact that, due to the use of a single reference country, variation in institutional distance between the reference country and partner countries is essentially equal to variation in the institutional profiles of these partner countries, making institutional distance and institutional profile effects indistinguishable. This research begins by demonstrating that the problem of profile – distance conflation is relevant for virtually all possible countries as reference points, and then showing how this problem is mitigated by using more than one country as reference points from which to calculate institutional distance. We conclude that current institutional research in international business is unable to explain how institutions matter for MNEs and that a more careful theoretical and empirical distinction between the effects of institutions and institutional distance on cross-border business activities is essential for pushing the institutional perspective in international business studies forward. Multiple reference point research designs are required to achieve this.